Rasch analysis of the participation scale (P-scale): usefulness of the P-scale to a rehabilitation services network - Mariana Angélica Peixoto Souza; Wendy Jane Coster; Marisa Cotta Mancini; Fabiana Caetano Martins Silva Dutra; Jessica Kramer; Rosana Ferreira Sampaio (BMC, 2017)
Abstract Background A person's participation is acknowledged as an important outcome of the rehabilitation process. The Participation Scale (P-Scale) is an instrument that was designed to assess the participation of individuals with a health condition or disability. The scale was developed in an effort to better describe the participation of people living in middle-income and low-income countries. The aim of this study was to use Rasch analysis to examine whether the Participation Scale is suitable to assess the perceived ability to take part in participation situations by patients with diverse levels of function. Methods The sample was comprised by 302 patients from a public rehabilitation services network. Participants had orthopaedic or neurological health conditions, were at least 18 years old, and completed the Participation Scale. Rasch analysis was conducted using the Winsteps software. Results The mean age of all participants was 45.5 years (standard deviation = 14.4), 52% were male, 86% had orthopaedic conditions, and 52% had chronic symptoms. Rasch analysis was performed using a dichotomous rating scale, and only one item showed misfit. Dimensionality analysis supported the existence of only one Rasch dimension. The person separation index was 1.51, and the item separation index was 6.38. Items N2 and N14 showed Differential Item Functioning between men and women. Items N6 and N12 showed Differential Item Functioning between acute and chronic conditions. The item difficulty range was −1.78 to 2.09 logits, while the sample ability range was −2.41 to 4.61 logits. Conclusions The P-Scale was found to be useful as a screening tool for participation problems reported by patients in a rehabilitation context, despite some issues that should be addressed to further improve the scale.